Ekonomi Islam untuk Keberlanjutan Umat Beragama (Studi Faktor yang Mempengaruhi Minat Anggota Non Muslim Dalam Menyimpan di BMT Artha Sejahtera Bantul) - Sartika Sari; Mohamad Faozy (Jurnal Rekoginisi Ekonomi Islam, 2022)
This research comprehensively examines how the Islamic economy is able to move the progress of religious communities, which in this case will be studied related to the factors that influence the interest of non-Muslim members in saving at KSPPS BMT Artha Sejahtera Srandakan Bantul Yogyakarta. The research method is field research with data collection through three stages, namely observation, interviews, and documentation. The data analysis uses the analysis from Miles and Huberman model, namely data presentation, data reduction, and drawing conclusions. The research results reveal that KSPPS BMT Artha Sejahtera Srandakan Bantul Yogyakarta is a non-governmental organization that was originally initiated by several groups of people who care about the fate of small and medium business actors. The factors that influence the interest of non-Muslim members in saving at BMT Artha Sejahtera Srandakan Bantul Yogyakarta from some respondents' perceptions consist of: location, service, profit sharing, company reputation, promotion, curiosity about the institution's sharia, close friends, and no administrative deductions. From the perception of the community, it is more dominant towards large profit sharing from the company. Therefore, the existence of BMT Artha Sejahtera is actually used as one of the pioneers of Islamic economics for the welfare of religious people at large.